Inhibitory Effect of PRMT5/MTA Inhibitor on MTAP‐Deficient Glioma May Be Influenced by Surrounding Normal Cells - Yunjie Wang; Xiaohui Sun; Runchen Ma; Xiaofan Zhang; Shengmin Ji; Zhaofeng Liu; Gangqiang Yang; Hongbo Wang; Peng Zhang; Jianzhao Zhang; Jingwei Tian (Cancer Medicine, 2024)
ABSTRACT Background Methylthioadenosine phosphorylase (MTAP) and protein arginine methyltransferase 5 (PRMT5) are considered to be a synthetic lethal pair of targets, due to the fact that deletion of MTAP leads to massive production of methylthioadenosine (MTA) decreasing the activity of PRMT5. In vitro and in vivo experiments have demonstrated that MRTX1719, a small molecule that selectively binds PRMT5/MTA complex, significantly inhibits the proliferation of MTAP‐deficient tumors and has a weak toxic effect on normal cells. However, it has been reported that MTAP‐deleted tumors did not significantly accumulate MTA in vivo due to metabolism of MTA by MTAP‐expressing stroma, which might lead to a diminished anti‐cancer effect of MRTX1719. Methods We first analyzed whether there were MTAP‐expressing normal intracerebral cells around MTAP‐deficient glioma tissues by paraffin‐embedded tissue microarray of human glioma specimens. Then, in vivo and in vitro models of MTAP‐deficient gliomas coexisting with neurons or glial cells were constructed for evaluating the effectiveness of the anti‐tumor effects of MRTX1719 in this setting. Results MTAP‐deficient gliomas were surrounded by a large number of MTAP‐expressing normal cells, and the presence of these cells significantly reduced the inhibitory effect of MRTX1719 on MTAP‐deficient glioma cells in vitro and in vivo. Conclusions Due to the complexity of the tumor environment in vivo, the anti‐tumor effects of PRMT5/MTA‐specific inhibitors may be somewhat attenuated, and their ability to achieve suitable therapeutic effects in the clinic might require more in‐depth studies.